Patient-specific organ and effective dose estimates in pediatric oncology computed tomography. (January 2018) - Gao, Yiming; Quinn, Brian; Pandit-Taskar, Neeta; Behr, Gerald; Mahmood, Usman; Long, Daniel; Xu, X. George; St. Germain, Jean; Dauer, Lawrence T.
Highlights: Organ and effective doses are estimated for over a thousand patients. Tube current modulation and patient body size variations are considered. Eye lens dose can be higher than nominal effect threshold in few repeated scans. Local CTDIvol and DLP 75th percentiles are mostly lower than national DRLs. Abstract: Purpose: Estimate organ and effective doses from computed tomography scans of pediatric oncologic patients using patient-specific information. Materials and Methods: With IRB approval patient-specific scan parameters and patient size obtained from DICOM images and vendor-provided dose monitoring application were obtained for a cross-sectional study of 1250 pediatric patients from 0 through 20 y-olds who underwent head, chest, abdomen-pelvis, or chest-abdomen-pelvis CT scans. Patients were categorized by age. Organ doses and effective doses were estimated using VirtualDose™ CT based on patient-specific information, tube current modulation (TCM), and age-specific realistic phantoms. CTDIvol, DLP, and dose results were compared with those reported in the literature. Results: CTDIvol and DLP varied widely as patient size varied. The 75th percentiles of CTDIvol and DLP were no greater than in the literature with the exception of head scans of 16–20 y-olds and of abdomen-pelvis scans of larger patients. Eye lens dose from a head scan was up to 69 mGy. Mean organ doses agreed with other studies at maximal difference of 38% for chest and 41% for abdomen-pelvis scans. Mean effective dose was generally higher for older patients. The highest effective doses were estimated for the 16–20 y-olds as: head 3.3 mSv, chest 4.1 mSv, abdomen-pelvis 10.0 mSv, chest-abdomen-pelvis 14.0 mSv. Conclusion: Patient-specific organ and effective doses have been estimated for pediatric oncologic patients from <1 through 20 y-olds. The effect of TCM was successfully accounted for in the estimates. Output parameters varied with patient size. CTDIvol and DLP results are useful for future protocol optimization.